New Semiempirical Equation Describing Evaporation and Condensation in Nonassociated Liquids - Mihail Yu. Gorbachev; Anatholy S. Dimoglo (Journal of Chemistry)
The consideration of the evaporating and condensing molecules’ interaction with the surface layer of nonassociated liquids made it possible to find an equation for relations between the saturated vapor pressure P, from one side, and surface tension, critical temperature, and molar volume of the liquids, from the other side. This equation takes into account the influence of intramolecular conformational transitions of evaporating molecules on the quantity of their energy barrier. There are two types of the condensation process for the nonassociated liquids: soft and hard molecular condensation. For some vapor molecules the surface layer of the liquids behaves as an impenetrable elastic film. In the case of evaporating molecules, their one-particle potential barrier caused by the surface molecules vibration is essentially higher for the conformationally flexible molecules than that for rigid ones.